Organizational learning and human motivation: a systemically represented relation - Garrido, Giovanna; Mendonça, Adriana Vazzoler; Silveira, Marco Antonio (Revista de Administração da UFSM, 2019)
This study aims to attribute a subjective focus on the analysis about the organizational learning, aiming to explore the main causal relations between learning and motivation in the organizational context. Classified as bibliographic research, both psychological and sociological, this study was based, mainly, in references available in Proquest and Scielo bases. The solidity of the debate was guaranteed by the anchoring of the study to two argumentative bases that, by the proposed analytical subjectivity, were considered influential in the process that was approached: the human essence and the hidden meaning of the work. Based on the consideration of both bases and on the adopted methodology, a map systemic was built including the main variables that surround the relation between learning and motivation phenomena, denoting the nature of this relation and the way as, related, impact on job productivity and on organizational performance. The built map was judged pertinent for enabling a better interpretation of the causal relations and of the reciprocal influences, direct or inversely proportional, between the variables of interest, subsidizing decisions and serving of orientation to managers involved on organizational process.